The Effect Of Capital Structure And Potential Bankruptcy On Share Prices In Building Construction Companies Listed On The Idx - Noni Ardian; Maya Macia Sari; Aulia; Evi Ariani (Yayasan Multidimensi Kreatif, 2023)
This study aims to determine the effect of capital structure and potential bankruptcy on share prices in building construction companies listed on the Indonesia Stock Exchange (IDX). The sampling technique used in this study was purposive sampling. The sample of this study was 17 building construction companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2022 period. There are three variables in this study, namely capital structure and bankruptcy potential as independent variables and stock prices as dependent variables. The method used in this study was panel data analysis. The results showed that the capital structure and potential for partial bankruptcy had a positive and significant effect on the share price of building construction companies for the 2019-2022 period. Simultaneously, capital structure and potential bankruptcy have a significant effect on the share price of building construction companies.